2015
DOI: 10.1002/2014jg002731
|View full text |Cite
|
Sign up to set email alerts
|

A study of the composition, characteristics, and origin of modern driftwood on the western coast of Nunavik (Quebec, Canada)

Abstract: Data concerning driftwood is of value to researchers in fields as diverse as oceanography, geomorphology, and human occupation. Yet studies on the subject in the Canadian Arctic have only recently been carried out, and the present study is the first in Nunavik (northeastern Canada). This paper documents the composition, characteristics, and origin of modern driftwood pieces on the beaches of the eastern coast of Hudson Bay. A total of 1057 samples from Ivujivik, Akulivik, Inukjuak, and Umiujaq were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…This is especially useful in brackish coastal environments in the proximity to major rivers and other sources of old carbon (Forman and Polyak, 1997;Dumond and Griffin 2002;Grigoriev et al, 2004). Alternatively, well-preserved driftwood can be dated by cross-correlating their tree-ring width measurements against independent, species-specific reference chronologies from the boreal catchments (Hellmann et al, 2013;, often yielding indication on the age of the outermost tree ring with a resolution of years to decades (Eggertson, 1994;Johansen, 1998;Steelandt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially useful in brackish coastal environments in the proximity to major rivers and other sources of old carbon (Forman and Polyak, 1997;Dumond and Griffin 2002;Grigoriev et al, 2004). Alternatively, well-preserved driftwood can be dated by cross-correlating their tree-ring width measurements against independent, species-specific reference chronologies from the boreal catchments (Hellmann et al, 2013;, often yielding indication on the age of the outermost tree ring with a resolution of years to decades (Eggertson, 1994;Johansen, 1998;Steelandt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While spruce (Picea sp.) largely dominates Arctic driftwood deposits (Alix, 2005;Steelandt et al, 2015), our results suggest that the high ratio of spruce charcoal regularly identified in archaeological sites of northwestern coastal Alaska where fat is omnipresent as fuel, may also result from issues of differential species preservation leading to an overrepresentation of spruce. However, it may also reflect a deliberate selection of the abundant spruce driftwood preferred for certain hearths functions.…”
Section: Tablementioning
confidence: 74%
“…Steelandt et al () have also shown that the buoyancy of wood decreases rapidly with a decrease in volume. Given the main water currents traveling north along the eastern shore of James Bay and Hudson Bay, Juniperus driftwood may have originated from the southern coastal region of Hudson Bay which is close to the tree line and near the village of Umiujaq (about 600 km south of Kuuvik Bay; Steelandt et al, ). Its scarcity is probably linked to the low volume of wood from this shrub species and the resulting low buoyancy.…”
Section: Discussionmentioning
confidence: 92%
“…Because the site is located in shrub tundra above the tree line for forest‐tundra species, and since no significant evolution of the tree line occurred over the last 3800 years in Nunavik (Payette & Lavoie, ), the charcoal likely originated from driftwood. However, Alix () noted the low prevalence of driftwood in the North American Arctic and there is almost no Juniperus driftwood in Steeland's collection, which includes driftwood from the Akulivik and Ivujivik regions (Steelandt, Marguerie, Bhiry, & Delwaide, ). Steelandt et al () have also shown that the buoyancy of wood decreases rapidly with a decrease in volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation